Faktor Yang Mempengaruhi Career Plan Mahasiswa Akuntansi Kota Surabaya - Albert Theodorus; Christian Christian; Sany Sany (Business Accounting Review, 2021)
This research was conducted to study the career plan of accounting student after graduating from university. The purpose of this study was to determine whether intrinsic factors, job-related considerations, career exposure and the influence of third person can influence accounting students' career plans. The study used a survey approach, where data consisted of 343 accounting students from five different universities in Surabaya, both private and public. Data were collected using questionnaires and were analysed using purposive sampling methods. The 343 respondents consisted of accounting students from Petra Christian University (163 respondents), Surabaya University (63 respondents), Ciputra University (46 respondents), Widya Mandala University (58 respondents), and Airlangga University (13 respondents). Data were analysed using SPSS software application. The results of this study show that job-related considerations, career exposure and the influence of third parties have a significant effect on the career plans of accounting students, whileintrinsic factors have a less significant effect on the career plans of accounting students.